Loci identified by a genome‐wide association study of carotid artery stenosis in the eMERGE network. Issue 1 (22nd September 2020) - Palmer, Melody R.; Kim, Daniel S.; Crosslin, David R.; Stanaway, Ian B.; Rosenthal, Elisabeth A.; Carrell, David S.; Cronkite, David J.; Gordon, Adam; Du, Xiaomeng; Li, Yatong K.; Williams, Marc S.; Weng, Chunhua; et al.
Abstract: Carotid artery atherosclerotic disease (CAAD) is a risk factor for stroke. We used a genome‐wide association (GWAS) approach to discover genetic variants associated with CAAD in participants in the electronic Medical Records and Genomics (eMERGE) Network. We identified adult CAAD cases with unilateral or bilateral carotid artery stenosis and controls without evidence of stenosis from electronic health records at eight eMERGE sites. We performed GWAS with a model adjusting for age, sex, study site, and genetic principal components of ancestry. In eMERGE we found 1793 CAAD cases and 17, 958 controls. Two loci reached genome‐wide significance, on chr6 in LPA (rs10455872, odds ratio [OR] (95% confidence interval [CI]) = 1.50 (1.30–1.73), p  = 2.1 × 10 −8 ) and on chr7, an intergenic single nucleotide variant (SNV; rs6952610, OR (95% CI) = 1.25 (1.16–1.36), p  = 4.3 × 10 −8 ). The chr7 association remained significant in the presence of the LPA SNV as a covariate. The LPA SNV was also associated with coronary heart disease (CHD; 4199 cases and 11, 679 controls) in this study (OR (95% CI) = 1.27 (1.13–1.43), p  = 5 × 10 −5 ) but the chr7 SNV was not (OR (95% CI) = 1.03 (0.97–1.09), p  = .37). Both variants replicated in UK Biobank. Elevated lipoprotein(a) concentrations ([Lp(a)]) and LPA variants associated with elevated [Lp(a)] have previously been associated with CAAD and CHD, including rs10455872. With electronic health record phenotypes in eMERGE and UKB, we replicated a previously known association and identified a novel locus associated with CAAD.